Підвищення точності вимірювання напруги негармонічного сигналу в умовах адитивної завади - Horbatyi, I. V. (PE "Politekhperiodika", Book and Journal Publishers, 2017)
The basic known methods of signal voltage measuring were considered. The circuit solutions used in the construction of digital voltmeters were analyzed. Their advantages and defects were analized. Method of direct assessment of alternating current voltage is proposed to improve by using the developed method for measuring root-mean-square value of alternating current voltage and the device for the realization of the method. It is set, that the use of improved method provides an increase of the inharmonious signal voltage measuring accuracy in conditions of additive noise. Circuit solutions that used for making of digital multimeter using the improved method for measuring of alternating current voltage were described.